The Rule of Law is An Important Factor and A Basic Condition of Civil Society - Ahror Ganiyevich Alijanov (International Journal on Human-Computing Studies, 2021)
One of the most important features of a democratic society is the equality of its members before the law, the Constitution and the equality of laws. Also, the ultimate goal of the Constitution and laws should be to ensure human rights and freedoms. This article highlights the priority of law as a factor and condition for the development of a civil society